Lymph node metastasis in early gastric adenocarcinoma in the United States of America - Pokala, Sridevi K.; Zhang, Chao; Chen, Zhengjia; Gamboa, Anthony M.; Cristofaro, Sarah L.; Keilin, Steven A.; Cai, Qiang; Willingham, Field F. (Endoscopy, 2018)
Background and study aims Localized approaches are being increasingly used in the management of early gastric adenocarcinoma; however, there are limited data on lymph node metastasis in the US population. This study examined the incidence and predictors of lymph node involvement for early-stage gastric adenocarcinomas in the USA.Patients and methods Data were abstracted from the national SEER database from 2004 to 2013. Exclusion criteria included: cases with unknown tumor characteristics, unknown patient characteristics, metastatic disease, neoadjuvant radiation, and lack of surgical resection or lymph node evaluation. Univariate and multivariable analyses were conducted to assess the relationship of tumor stage, grade, and size, and patient sex, race, and age with nodal involvement. Results 43 769 cases of gastric adenocarcinoma were initially abstracted. After exclusions, 1577 patients remained for analysis. Multivariable analysis revealed that tumor stage (P < 0.001), grade (P = 0.008), and size (P < 0.001) were independent predictors of nodal metastasis. For low grade T1a tumors, nodal metastasis was present in 1.7 %, 1.7 %, 4.5 %, 4.1 %, and 20 % of tumors 0 – 1 cm, 1 – 2 cm, 2 – 3 cm, 3 – 4 cm, and ≥ 4 cm in size, respectively (P < 0.001), and in 8.4 %, 18.0 %, 19.5 %, 22.0 %, and 35.8 % of T1b tumors, respectively (P < 0.001).Conclusions Low grade T1a tumors < 4 cm in size have low rates of nodal metastasis in the US population and may warrant consideration for local resection. Larger, higher grade T1b tumors have high rates of nodal metastasis in the US population and lymph node dissection may be indicated for patients who are surgical candidates.